PERSONAL TEACHING PHILOSOPHY CALON GURU SEKOLAH DASAR: ANTARA TEORI DAN PRAKTIK - Pamungkas, Aan; Muslim, Suyitno; Djatmiko, Wisnu (Jurusan Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2024)
This study aims to explore and analyse the Personal Teaching Philosophy of pre-service primary school teachers by emphasising the relationship between theory and practice in the development of their teaching philosophy. Through a literature review approach, this study examines various relevant literatures in the last five years, both national and international journals, to understand how pre-service primary school teachers form, develop and apply their Personal Teaching Philosophy in the classroom. The results of the review show that the Personal Teaching Philosophy is a reflection of pre-service teachers' personal values that are influenced by educational theories such as constructivism, behaviourism and humanism. However, in practice, prospective teachers often face challenges when applying these theories in diverse and dynamic classrooms. Continuous reflection and practical teaching experience are important factors in helping pre-service teachers adapt and adjust their Personal Teaching Philosophy according to the real situation in the field. This study suggests that Teacher Education strengthen the integration between theory and practice through more intensive field experiences, structured reflection training, and closer collaboration with student teachers. In addition, this study also encourages further research on the development of Personal Teaching Philosophy over time to understand its influence on teaching quality. The findings are expected to provide insights for the development of more effective and relevant pre-service teacher education programmes.